Selecting the Optimal Web Service Composition Based on QoS - Al-Shareef, Shrouq; Saheb, Mahmoud Hasan (Discoveries in Agriculture and Food Sciences, 2019)
The fast spread of web services in our businesses and day-to-day lives has made QoS an essential aspect for both the service providers and consumers. The main problem is how the consumer obtains a high comprehensive quality composite service when there are a large number of web services available; the choice of the optimal path depends on the QoS for every atomic service. Our contribution is studying the influence of the reputation factor in the process of selecting the optimal path in the absence of one of four factors (Availability, Reliability, Response Time, and Price) and the possibility of covering for this absence. We have used the reputation factor when calculating the QoS by using artificial bee colony algorithm for selecting the optimal web service composition; then we analyzed the impact of reputation on the process of selecting web service composition in terms of the QoS and accuracy of the solution. Also, we studied the impact of the reputation factor in the case of the absence of one of the four factors through three experiments and a set of comparisons. The result was that the reputation factor could cover factors such as availability, Response Time, and technical support. We used multiple linear regression and polynomial regression to show the prediction of the reputation factor using the four other factors. The result had higher confidence when we used multiple polynomial regression where the Residual Sum of Squares (RSS) was less than the multiple linear regression. In addition, we analyzed the association between reputation and the four other factors using ANOVA test; the result indicates that there is a significant association between reputation and (availability, response time, and price), but the association is not significant with the reliability.